2012
DOI: 10.1371/journal.pone.0051467
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study of Relational Learning Capacity in Honeybees (Apis mellifera) and Stingless Bees (Melipona rufiventris)

Abstract: BackgroundLearning of arbitrary relations is the capacity to acquire knowledge about associations between events or stimuli that do not share any similarities, and use this knowledge to make behavioural choices. This capacity is well documented in humans and vertebrates, and there is some evidence it exists in the honeybee (Apis mellifera). However, little is known about whether the ability for relational learning extends to other invertebrates, although many insects have been shown to possess excellent learni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 41 publications
1
12
0
15
Order By: Relevance
“…Such discriminative ability extends to the genus Melipona (Menzel, Ventura, Werner, Joaquim, & Backhaus, 1989; Moreno, de Souza, & Reinhard, 2012;Pessotti, 1972), which was used in the present study. Bees can also master discriminative tasks that involve stimuli of different sensory modalities such as colors and odors (Giurfa et al, 2001;Reinhard, Srinivasan, Guez, & Zhang, 2004;Srinivasan, Zhang, & Zhu, 1998), and tasks that involve arbitrary relations between colors and temperatures (Dyer, Whitney, Arnold, Glover, & Chittka, 2006).…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Such discriminative ability extends to the genus Melipona (Menzel, Ventura, Werner, Joaquim, & Backhaus, 1989; Moreno, de Souza, & Reinhard, 2012;Pessotti, 1972), which was used in the present study. Bees can also master discriminative tasks that involve stimuli of different sensory modalities such as colors and odors (Giurfa et al, 2001;Reinhard, Srinivasan, Guez, & Zhang, 2004;Srinivasan, Zhang, & Zhu, 1998), and tasks that involve arbitrary relations between colors and temperatures (Dyer, Whitney, Arnold, Glover, & Chittka, 2006).…”
Section: Introductionmentioning
confidence: 83%
“…In fact, the results for baseline acquisition were somewhat unexpected for this experiment. Prior studies of visual discriminative learning in bees indicated that less than 100 training trials were required to establish a robust discriminative baseline (Giurfa et al, 2001;Moreno et al, 2012;Pessotti, 1972). For example, in the study by Moreno et al,16 bees received simple discrimination training with horizontal vs. vertical patterns and blue vs. yellow colors.…”
Section: Discussionmentioning
confidence: 99%
“…Tipicamente, esses estudos são conduzidos em laboratórios nos quais uma ou mais colmeias são posicionadas junto a janelas da instalação, e algum aparato experimental é montado no interior do laboratório (e.g., Moreno, de Souza, & Reinhard, 2012). Desse modo, as abelhas não ficam confinadas.…”
unclassified
“…Vários estudos também demonstraram a discriminação entre formas -padrões em preto e branco, ou figuras de formas diferentes mas com a mesma cor (e.g., Gould, 1985Gould, , 1986Horridge, 2000Horridge, , 2007Lehrer, & Campan, 2005;Lehrer et al, 1995;Moreno et al, 2012;Pessotti, & Carli-Gomes, 1981;Rodriguez, Gumbert, de Ibarra, Hunze, & Giurfa, 2004;Zhang, Srinivasan, & Collett, 1995).…”
unclassified
See 1 more Smart Citation